SIMULASI UJI TAK MERUSAK PELAT ELEMEN BAKAR PASCA IRADIASI MENGGUNAKAN METODE PENETRANT TEST - Wicaksono, Yusuf Gigih; Rahmatullah, Helmi Fauzi; Artika, Refa; Ismarwanti, Sri; Sigit, Rohmad (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2022)
The post-irradiation examination aims to determine the performance of nuclear fuel during irradiation in the reactor. Non-destructive tests at the Radiometallurgical Installation include visual observations, digital X-ray radiography, and ultrasonic tests for inspection of potential defects or anomalies in the fuel plate (PEB). Limitations in the detection of surface defects necessitate other nondestructive test methods, i.e., to simulate the use of the penetrant test method on the PEB dummy. The purpose of this simulation is to determine the ability of the penetrant test method to complement the non-destructive test data that has been previously conducted as well as to review the capability of the hot cell in applying the method. The simulation was carried out using a dummy PEB with artificial defects and used water-washable visible penetrant and solvent-removable visible penetrant. The simulation stages for implementing the penetrant test include precleaning, applying the penetrant, dwell time, removing the penetrant, applying developer, inspection, and post-cleaning. The simulation results with the penetrant test method are able to detect surface defects in the form of cracks and porosity, but cannot detect blister defects. Based on the simulation results, it can be concluded that the penetrant test can be an alternative method to complement the non-destructive test using X-ray and ultrasonic radiographic methods. In addition, to accommodate the application of the penetrant test method in IRM hot cells, it is necessary to develop support facilities while still paying attention to ease of handling and safety systems.